Exploring the Extent in the Visual Field of the Honeycomb and Extinction Illusions. (July 2019) - Bertamini, Marco; Cretenoud, Aline F.; Herzog, Michael H.
There are situations in which what is perceived in central vision is different to what is perceived in the periphery, even though the stimulus display is uniform. Here, we studied two cases, known as the Extinction illusion and the Honeycomb illusion, involving small disks and lines, respectively, presented over a large extent of the visual field. Disks and lines are visible in the periphery on their own, but they become invisible when they are presented as part of a pattern (grid). Observers ( N = 56) adjusted a circular probe to report the size of the region in which they had seen the lines or the disks. Different images had black or white lines/disks, and we included control stimuli in which these features were spatially separated from the regular grid of squares. We confirmed that the illusion was experienced by the majority of observers and is dependent on the interaction between the elements (i.e., the lines/disks have to be near the squares). We found a dissociation between the two illusions in the dependence on contrast polarity suggesting different mechanisms. We analysed the variability between individuals with respect to schizotypical and autistic-spectrum traits (short version of the Oxford-Liverpool Inventory of Feelings and Experiences [O-LIFE] questionnaire and the Autistic Quotient, respectively) but found no significant relationships. We discuss how illusions relative to what observers are aware of in the periphery may offer a unique tool to study visual awareness.